2021
DOI: 10.1111/1750-3841.15676
|View full text |Cite
|
Sign up to set email alerts
|

Region identification of Xinyang Maojian tea using UHPLC‐Q‐TOF/MS‐based metabolomics coupled with multivariate statistical analyses

Abstract: Xinyang Maojian tea is a kind of famous roasted green tea produced in the middle of China. Ultra‐high performance liquid chromatography‐quadrupole time of flight‐mass spectrometry (UHPLC‐Q‐TOF/MS)‐based metabolomics coupled with multivariate statistical analyses, including principal component analysis (PCA) and hierarchical cluster analysis (HCA), were carried out in XMMJTs collected from Luoshan, Shangcheng, and Shihe Counties, respectively. Additionally, seven catechins, four flavonoids, two purine alkaloids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Meanwhile, α-ionone had the maximum OAV value (215.29 ± 10.72) in the GX sample and the minimum OAV value (26.52 ± 5.23) in the SX sample. Previous literature ( Wang et al, 2021 ) stated that the continuous postfermentation of dark tea caused the degradation of carotenoids, leading to the accumulation of α- and β-ionones as demonstrated by our findings. Ionones (including α- and β-forms) were reported to have a remarkable effect on the aroma of teas ( Zhou et al, 2019 ), and the different ionone values of FBT samples could be used to discriminate teas from diverse production regions.…”
Section: Resultssupporting
confidence: 80%
“…Meanwhile, α-ionone had the maximum OAV value (215.29 ± 10.72) in the GX sample and the minimum OAV value (26.52 ± 5.23) in the SX sample. Previous literature ( Wang et al, 2021 ) stated that the continuous postfermentation of dark tea caused the degradation of carotenoids, leading to the accumulation of α- and β-ionones as demonstrated by our findings. Ionones (including α- and β-forms) were reported to have a remarkable effect on the aroma of teas ( Zhou et al, 2019 ), and the different ionone values of FBT samples could be used to discriminate teas from diverse production regions.…”
Section: Resultssupporting
confidence: 80%
“…A few studies have focused on the volatile compounds of XYMJ green tea [ 14 , 15 ] and the key odorants responsible for the XYMJ green tea have been identified [ 16 , 17 ]. To get a deeper insight into the effect of the single manufacturing process on the XYMJ green tea aroma formation, the key odorants and their dynamic changes during manufacturing processes from tea shoots to drying must be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The reason might be that the new variables generated in the dimensionality reduction process of PCA produced different results. The clusters-B, C, E, F, and G included seven, twenty-one, two, nine, and eleven TTs, respectively, among which clusters-F and G corresponded to the sample distribution in the gray and green circles in Figure 1 a,b, respectively; while other samples in Figure 1 b corresponded to clusters-B, C, and E. In short, PCA and HCA can be used to explain whether teas could be distinguished according to season, year, production place, processing technologies, and category variations [ 32 , 33 , 34 , 35 ]. In this study, the results revealed that phytochemicals were the dominating influence factors in the classification of AT and TT, which could be used as identification indicators of both.…”
Section: Resultsmentioning
confidence: 99%